The influence of BMI, physical fitness, and clean and healthy living behavior on student learning outcomes - Sepriani, Rika; Pratiwi, Monica Dara; Sepriadi, Sepriadi; Sabillah, Muhamad Ichsan (Jurnal Pendidikan Jasmani Indonesia, 2025)
This study aims to optimize the learning outcomes of Physical Education, Health, and Sports through the values of body mass index, physical fitness, and clean and healthy living behavior of students in junior high schools. This study is a type of descriptive quantitative research that uses path analysis techniques. Data was collected by measuring students' height and weight, using the TKSI phase D test, using the PHBS questionnaire, and measuring students' PJOK scores. Data analysis was used with path analysis with a significance level of Î± = 0.05. The instrument used to measure nutritional status variables was a BMI test. To measure physical fitness, the TKJI test was used. For learning outcomes, it was done by collecting students' report card scores. The results of the research that has been carried out are 1) there is no relationship between BMI and PHBS with a sig value of 0.397. 2) There is no relationship between physical fitness and PHBS with a sig value of 0.397. 3) The contribution given by BMI and KJ is 3.3%. 4) Indirectly, BMI through PHBS on learning outcomes does not have a significant effect with a value of -0.014. 5) Indirectly, KJ through PHBS on learning outcomes has a significant positive effect with a value of -0.129. 6) The contribution given by IMT, KJ, and PHBS together to learning outcomes is 20.9%.